If You Love the Forest, then Do Not Kill the Trees: Health Care and a Place for the Particular. Issue 3 (9th June 2021) - Colgrove, Nicholas
Abstract: There are numerous ways in which "the particular"—particular individuals (whether patients or physicians), particular ideologies, values, beliefs, and perspectives—are sometimes overlooked, ignored, or even driven out of the healthcare profession. In many such cases, this is bad for patients, practitioners, and the profession (or so I argue). Hence, we should seek to find a place for the particular in health care. Specific topics that I examine in this essay include distribution of health care based on the particular needs of patients, the importance of protecting physicians' right to conscientious objection, the value in tolerating a plurality of moral and medical perspectives within the field, and more. Ultimately, as the imagery in the essay's title suggests, I argue that if one cares about the "well-being" of the medical profession (generally), then one should seek to avoid destroying the many diverse and particular entities that constitute it.